Monitoring and analysis part of river bank using unmanned aerial vehicle [UAV] at Terusan Besar, Jitra / Mohammad Amin Mohd Asli - Mohd Asli, Mohammad Amin (2019)
The unmanned aerial vehicle today not just as hobby but for mapping with the photogrammetry concept, combining aerial photo and aerial mapping. The ability of UAV is to capture the aerial image with the information of the ground control point that can be produce in elevation model. The purpose of this thesis was to produce the Digital Surface Model and Digital Terrain Model of the study area with the aim to apply photogrammetry concept in aerial mapping using unmanned aerial vehicle for the river bank in Digital Surface Model and Digital Terrain Model at Kampong Lubuk Batu, Kedah. The objective of this thesis consist with three which is producing DSM and DTM, generating river bank profile and to evaluate of the two source of data. The methodology consist with the data was achieved by processing using the software. Flight control algorithms to guide a vehicle through waypoint based flight paths and loiter about a point were implemented using direction fields. The result will show the changes of the river bank between the current and previous image captured data in 2015